Cardiac transplantation in adults with congenital heart disease. Issue 15 (16th July 2010) - Irving, C; Parry, G; O'Sullivan, J; Dark, J H; Kirk, R; Crossland, D S; Chaudhari, M; Griselli, M; Hamilton, J R L; Hasan, A
Abstract : Background: Due to increasing success with repair or palliation in childhood, there is a rapidly growing population of adult patients with complex congenital heart disease who may require transplantation. There remains little data on outcomes of cardiac transplantation in this group. Methods: 38 orthotopic cardiac transplants were performed in 37 patients (18 men) ≥18 years of age with congenital heart disease (CHD) from 1988 to 2009 in our institution. Outcomes were reviewed using medical records and transplant databases. Results: 15 patients (41%) had univentricular and 22 (59%) biventricular physiology. The biggest group was transposition of the great arteries following atrial switch in eight patients (22%). Six (16%) had no previous surgical intervention. Mean age at transplant was 33.5 years (range 19.1–59.9 years). 11 patients (30%) required additional surgical procedures at transplant. 16 (43%) died, 12 early and 4 late deaths (1.8, 2.4, 2.7 and 7 years). Survival was 70% at 30 days, 68% at 1 year, 58% at 5 years and 53% at 10 and 15 years. Outcome improved in later eras with reduction in 30-day mortality from 50% to 18% and increase in 5-year survival from 50% to 69%. Two patients developed post-transplant lymphoproliferative disease. None required long-term renal replacement therapy. One patient was re-transplanted for cardiac allograft vasculopathy. Conclusions: While operative mortality following cardiac transplantation for adult congenital heart disease is higher than for other diagnostic groups, long-term survival is good and comparable to patients without CHD. Disappointing early results are improved with increasing experience.